Variation and Predictors of COVID-19 Mortality in Hospitalized Cases in West Sumatra Province, Indonesia: A Retrospective Observational Study - Djafri, Defriman; Putri, Ade Suzana Eka; Pradipta, Yudi (Kesmas, 2024)
During 2020, the year of the COVID-19 pandemic, different Indonesian provinces had different numbers of COVID-19 infections and fatalities, particularly in West Sumatra Province. This study aimed to investigate the variation of confirmed COVID-19 cases and determine predictors of mortality in hospitalized patients across districts in West Sumatra Province. A retrospective observational study was conducted during the COVID-19 pandemic. From March 2020 to June 2021, 46,005 confirmed cases were collected in the province, of which 42,308 were hospitalized and analyzed. Confirmed cases and deaths were compared by geographic location using spatial analysis. The risk predictors of death were estimated using logistic regression. COVID-19 incidence and mortality varied across cities/districts, with less than 1,000 confirmed cases appearing to be the lowest number. A distinct pattern was visible nonetheless when the incidence density of confirmed cases and deaths was higher. Acute respiratory distress syndrome during the COVID-19 treatment had a higher risk of death (OR = 75.2, 95% CI: 25.6–250). The most significant predictors of death in terms of comorbidity were pneumonia, followed by cancer, chronic obstructive pulmonary disease, diabetes, cardiac disease, and hypertension.